Determination of new psychoactive substances in forensic samples by gas chromatography coupled to mass spectrometry - Almeida, Pedro Rafael Gonçalves de (2021)
The term “new” for new psychoactive substances does not only refers to the newly synthesized compounds, but also to the ones used in an inappropriate way. These substances are produced to mimic the effects of the already controlled substances, like cocaine and amphetamine and despite the efforts to reduce their appearance, with the easy access to information and purchase, their presence in the streets had an alarming increase. For this work, it was developed and validated an analytical methodology to determine a group of eight synthetic cathinones (cathinone, flephedrone, buphedrone, a-PVP, methylone, ethylone, pentylone and MDPV) and three phenethylamines (4-MTA, 2C-P and dragonFLY). It was used blood as a biological matrix and deutered internal standards (amphetamine-d6, methamphetamine-d9, 3,4-methylenedioxymethamphetamine-d5, 3,4-Methylenedioxy-Nethylamphetamine-d5 and N-Methyl-1-(1,3-benzodioxol-5-yl)-2-butanamine-d5). The preparation of the sample consisted in a mixed-mode solid phase extraction followed by a fast derivatization process utilizing a microwave and the N-Methyl-bis(trifluoroacetamide) as the derivatization reagent, and the extracts were then analysed by gas chromatography-mass spectrometry operating in electron ionization mode analysis. The procedure was validated following the Scientific Working Group of Forensic Toxicology guidelines and the parameters studied were selectivity, linearity, limits of detection and quantification, intra- and interday precision and trueness, extraction efficiency and stability. The methodology presented linearity between 5-500 ng/mL for cathinone, buphedrone, 4-MTA, methylone, 2C-P and dragonFLY, 10-500 ng/mL for flephedrone, ethylone, pentylone and MDPV and 40-500 ng/mL for a-PVP, with determination coefficients above 0.99 for all substances. The limits of detection and quantification ranged between 5 ng/mL and 40 ng/mL, depending on the substance. For intra-day and interday precision the values of coefficient of variations varied between 1.1 and 8.6% and extraction efficiencies ranged from 70.3 to 116.6%. The method was subsequently applied to more than one hundred authentic samples of the Laboratory of Chemistry and Forensic Toxicology, Centre Branch, of the National Institute of Legal Medicine and Forensic Sciences, Portugal.